Estudo das propriedades superficiais e eletrocatalíticas de misturas ternárias de óxidos:o sistema RuO2 + PdO + TiO2 - Miranda, Celio Gomes (2000)
To contribute to the development of electrode materiais of technological interest we decided to investigate the PdO + RuO2 + TiO2 System. Electrode coatings were prepared by the classical thermal decomposition route of the chloride precursor salts dissolved in HC1 1:1 (v/v). Film composition was decided based on Chemiometric principies. Based on uv-visible spectrophometric results it was shown that the RuCh precursor solution consisted of the Ru(III) and Ru(IV) oxidation States, mainly as aquo/cloro complexes. The PdCl2 precursor solution containe paladium in the +2 and +4 oxidation States, probably as cloro complexes. The species in the TiCU precursor solution are mainly hydroxi/cloro or aquo/hydroxi cloro complexes. Surface and electrocatalytic properties of the electrode materiais were investigated “z>? situ” by open circuit potential measurements and cyclic voltammetry. Up to 65 potential cycles were recorded (20mV.s_1; 1.0 mol.dm'3 HCIO4) covering the 0.4-1.4V/r.h.e. potential range. The sequence for the electrochemically active surface area of the pure oxides was established: ARuo2 > APdo > Atío2. The investigation of the influence of the anodic switching potential on the voltammetric behaviour showed that for both pure PdO and its mixtures with the other components, the several oxides present (PdO, PdO2) are reduced to metallic Pd in a single peak with EP;C depending on E^. During the anodic sweep Pd(0), formed during the cathodic sweep, is oxidized in two two-electron steps: (1) in the low overpotential region to stable PdO is formed; (2) at higher anodic potentials to unstable PdO2. The OER starts at ~1.55V/r.h.e at the Ti/PdO electrode being shifted anodically by -0.10V on the Ti/RuO2 electrode. Ti/TiO2 passivation start at 2.2V/r.h.e. The best global electrocatalytic activity was observed for the Ti/Ruo.sPdo.sOi.s nominal composition. The influence of the cathodic switching potential as well as the time of conditioning of the surface at 0.4V/r.h.e. (tcOnd: 0”, 30”, 60”, 120” and 300”) on the voltammetric behaviour showed PdO is reduced to Pd(0) in the potential interval comprised between 0.25 - 0.5V/r.h.e. Pd(0) showed peaks due to Hads/Hdesor, involving the outer surface of the coating, together with high intensi peaks due to the absorption/desorption of H, involving the bulk of the coating. The hydrogen evolution reaction, HER, only starts after the coating is saturated with HabSOrbed. All PdO containing films show this phenomenon. In the case of the pure Ti/RuO2 film no evidence was found of H adsorption preceding the HER. The reduction of Ru(III) to Ru(II) at potentials more cathodic then 0.4V/r.h.e. cannot be excluded. In the case of the Ti/TiO2 electrode, the onlyevent occurring in the potential region between 0.1-0.4V/r.h.e. is the charging of the double layer. The onset of the HER is observed at more cathodic potentials then - 0.35V/r.h.e. At even more cathodic potentials the reduction of Ti(IV) to Ti(III) occurs. The surface electrochemistry of PdO-containing mixtures is governed by the Pd-electrochemistry. The best global electrocatalytic activity for the HER was obtained for the coating with having a Ti/Ruo.sPdo.sOi.s nominal composition with a current density of 220mA.cm'2 at -O.lOOV/r.h.e.